Mating dynamics in a nematode with three sexes and its evolutionary implications. - Chaudhuri, Jyotiska; Bose, Neelanjan; Tandonnet, Sophie; Adams, Sally; Zuco, Giusy; Kache, Vikas; Parihar, Manish; Von Reuss, Stephan; Schroeder, Frank C; Pires-daSilva, Andre (My University, 2015)
Nematodes have diverse reproductive strategies, which make them ideal subjects for comparative studies to address how mating systems evolve. Here we present the sex ratios and mating dynamics of the free-living nematode Rhabditis sp. SB347, in which males, females and hermaphrodites co-exist. The three sexes are produced by both selfing and outcrossing, and females tend to appear early in a mother's progeny. Males prefer mating with females over hermaphrodites, which our results suggest is related to the female-specific production of the sex pheromones ascr#1 and ascr#9. We discuss the parallels between this system and that of parasitic nematodes that exhibit alternation between uniparental and biparental reproduction.